Adoption of digital money (e-wallet) in the post COVID-19 era: The moderating role of low distribution charges and low transit time in impulsive buying: A developing country perspective - Wei, Qing; Xiao, Wendong; Yaqub, Rana Muhammad Shahid; Irfan, Muhammad; Murad, Muhammad; Yaqub, Muhammad Zafar (Frontiers in Environmental Science, 2023)
The objective of this study was to demonstrate to what extent low distribution charges and low transit time is contributing to impulsive buying when customers have the opportunity of digital money in Pakistan for environment sustainability. Online purchasing is increasing because customers are shifting to a digital wallet and digital money as these services are provided by different microfinance and other commercial banking sectors, and different online brands are working in Pakistan to support the environmental sustainability. Importantly, 650 questionnaires were distributed to the respondents with an expected response rate of 40%. The scope of this study is limited to the online businesses and brands that are working to provide products and services to the Pakistani people with the help of digital money and digital transaction. Further, this study concludes that the low transit time and load distribution charges must be considered by the online businesses and brands working in Pakistan to ensure productivity and capture a big market share of impulsive buying in Pakistan. Also, the current study contributes a theoretical framework to the knowledge and literature related to impulsive buying. Significantly, this study provides significant future directions that are important to consider for the coming study to focus and contribute effectively.